2016
DOI: 10.5812/hepatmon.32971
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Viruses B and D and Human Immunodeficiency Virus Infections in Hemodialysis Patients in the South of Iran: Prevalence and Genotypes

Abstract: BackgroundHepatitis B virus (HBV), hepatitis D virus (HDV), and human immunodeficiency virus (HIV) are transmitted by blood transfusion. Thus, hemodialysis (HD) patients are more prone to become the carriers of these infections due to their treatment demands.ObjectivesThe aim of this study was to assess the prevalence of HBV and HIV infections among HD patients in Bandar Abbas, Iran, 2015.Patients and MethodsA total of 153 patients with chronic renal failure undergoing HD at Shahid Mohammadi hospital in Bandar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Another study showed that the use of the same dialysis equipment and machines strongly correlates with hepatitis B prevalence (9). Another study also reported a significant correlation between HDVAb positivity and the number of hemodialysis sessions per month (30).…”
Section: P R O O Fmentioning
confidence: 83%
See 4 more Smart Citations
“…Another study showed that the use of the same dialysis equipment and machines strongly correlates with hepatitis B prevalence (9). Another study also reported a significant correlation between HDVAb positivity and the number of hemodialysis sessions per month (30).…”
Section: P R O O Fmentioning
confidence: 83%
“…Another study on patients, who were receiving hemodialysis in Tehran found that 7.5% of the cases were HBsAg-positive and 33.3% of HBsAg-positive patients were HDVAb-positive (8). However, a study on 153 hemodialysis patients in the south of Iran showed that nine (5.88%) were HBsAg-positive and none suffered from hepatitis D (9).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations